Guess What You Had for Breakfast This Morning 1980 -- 2010 - Center for Health, Environment, and Justice (Tufts Archival Research Center, 2017)
Poster produced by the Center for Health, Environment, and Justice educating on the presences and effects of dioxin in the food supply.